Connections between preschoolers' temperament traits and social behaviors as observed in a preschool setting. Issue 2 (7th November 2017) - Gornik, Allison E.; Neal, Jennifer W.; Lo, Sharon L.; Durbin, C. Emily
Abstract: A growing literature has focused on the role children's temperament traits play in social behavior, but associations have traditionally been explored through informant report. We utilized a longitudinal, observational approach to (a) examine how children's traits related to their social behaviors when aggregated across the school year; (b) explore how traits and social behavior relate to children's age and sex; and (c) test how prior traits predicted subsequent change in solitary, reticent, and social play, above and beyond mean‐level change in play behavior over the course of the year. Fifty‐three children were observed in their preschool classroom, where coders rated children's traits and social behaviors over the course of one school year (N = 26, 673 observations). Results found positive age‐related associations for positive emotionality (PE) and social play. In addition, aggregated traits explained a significant amount of the variance for every social behavior. Prior levels of lower PE, higher negative emotionality (NE), and higher effortful control (EC) predicted more subsequent time spent in reticent play, while NE and EC approached significance as predictors of solitary play. These results emphasize the role of early disposition on mean levels and rates of change in social behavior in a classroom.